Feeding Strategies to Mitigate Enteric Methane Emission from Ruminants in Grassland Systems - Vargas, Juan; Ungerfeld, Emilio M.; Muñoz, Camila; DiLorenzo, Nicolas (MDPI, 2022)
Ruminants produce approximately 30% of total anthropogenic methane emissions globally. The objective of this manuscript was to review nutritional enteric methane abatement practices for ruminants that are applicable under grazing conditions. A total of 1548 peer-reviewed research articles related to the abatement of enteric methane emissions were retrieved and classified into four categories: non-experimental, in vitro, in vivo confined, and in vivo grazing. The methane abatement strategies for grazing systems were arranged into grazing management and supplementation practices. Only 9% of the retrieved papers have been conducted under grazing conditions. Eight grazing management practices have been evaluated to reduce methane emissions. Decreasing the pre-grazing herbage mass reduced the methane emission per unit of product. Other grazing management practices such as increased stocking rate, decreased forage maturity, rotational stocking, and incorporating tannin-containing or non-tannin-containing feeds showed contradictory results. Nitrogen fertilization or silvopastoral systems did not modify methane emissions. Conversely, supplementation practices in grazing conditions showed contradictory responses on methane emissions. Lipid supplementation showed promising results and suggests applicability under grazing conditions. Identifying and implementing grazing strategies and supplementation practices under grazing conditions is required to increase efficiency and reduce the environmental impact of these systems.